Perancangan Sistem Aplikasi Monitoring Barang menggunakanBarcodeBerbasis Android. (study kasus Toko Chacha cell ITC Cempaka mas) - Rian gustini; Firman Noor Hasan (Prosiding Seminar Nasional Teknoka, 2020)
Cha-cha cell ITC Cempaka Mas is one of the mobile buying and selling stores that have not utilizes a computerized database system so that it still checks the price and stock of items manually andthesales database is still using thick books. This checking process makes buying and selling transactions takea long time because checking items and prices are still done manually. Therefore/that's why, the author approves an application that makes it easy to check inventory. This application uses the prototypingmethod which is tested by the Black Box test method and from the results of interviews with the owner regarding the application that provides employees in checking stock of items sold and items bought.